Age-Related Functional and Expressional Changes in Efflux Pathways at the Blood-Brain Barrier - Erdő, Franciska; Krajcsi, Péter (Frontiers in Aging Neuroscience, 2019)
During the last decade, several articles have reported a relationship between advanced age and changes in the integrity of the blood-brain barrier (BBB). These changes were manifested not only in the morphology and structure of the cerebral microvessels but also in the expression and function of the transporter proteins in the luminal and basolateral surfaces of the capillary endothelial cells. Age-associated downregulation of the efflux pumps ATP-binding cassette transporters (ABC transporters) resulted in increased permeability and greater brain exposure to different xenobiotics and their possible toxicity. In age-related neurodegenerative pathologies like Alzheimer’s disease (AD), the amyloid-β (Aβ) clearance decreased due to P-glycoprotein (P-gp) dysfunction, leading to higher brain exposure. In stroke, however, an enhanced P-gp function was reported in the cerebral capillaries, making it even more difficult to perform effective neuroprotective therapy in the infarcted brain area. This mini-review article focuses on the efflux functions of the transporters and receptors of the BBB in age-related brain pathologies and also in healthy aging.